Prevalence of errors causing events allegedly attributable to vaccination/immunization: systematic review and meta-analysis - Laís Oliveira de Moraes Tavares; Marla Ariana Silva; Bianca Rabelo de Oliveira; Gabriela Gonçalves Amaral; Eliete Albano de Azevedo Guimarães; Renê Oliveira Couto; Valéria Conceição de Oliveira (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To identify the prevalence of errors that caused events supposedly attributable to vaccination or immunization. Method: Systematic literature review with meta-analysis carried out on the Medline, Cochrane Library, Cinahl, Web of Science, Lilacs, Scopus; Embase; Open Grey; Google Scholar; and Grey Lit databases; with studies that presented the prevalence of immunization errors that caused events or that provided data that allowed this indicator to be calculated. Results: We evaluated 11 articles published between 2010 and 2021, indicating a prevalence of 0.044 errors per 10,000 doses administered (n=762; CI95%: 0.026 - 0.075; I2 = 99%, p < 0.01). The prevalence was higher in children under 5 (0.334 / 10,000 doses; n=14). The predominant events were fever, local pain, edema and redness. Conclusion: A low prevalence of errors causing events was identified. However, events supposedly attributable to vaccination or immunization can contribute to vaccine hesitancy and, consequently, have an impact on vaccination coverage.